Organizational factors associated with adherence to low tidal volume ventilation: a secondary analysis of the CHECKLIST-ICU database - Midega, TD; Bozza, FA; Machado, FR; Guimarães, HP; Salluh, JI; Nassar, AP; Normílio-Silva, K; Schultz, MJ; Cavalcanti, AB; Serpa Neto, A (Springer, 2020)
Background Survival benefit from low tidal volume (VT) ventilation (LTVV) has been demonstrated for patients with acute respiratory distress syndrome (ARDS), and patients not having ARDS could also benefit from this strategy. Organizational factors may play a role on adherence to LTVV. The present study aimed to identify organizational factors with an independent association with adherence to LTVV. Methods Secondary analysis of the database of a multicenter two-phase study (prospective cohort followed by a cluster-randomized trial) performed in 118 Brazilian intensive care units. Patients under mechanical ventilation at day 2 were included. LTVV was defined as a VT ≤ 8 ml/kg PBW on the second day of ventilation. Data on the type and number of beds of the hospital, teaching status, nursing, respiratory therapists and physician staffing, use of structured checklist, and presence of protocols were tested. A multivariable mixed-effect model was used to assess the association between organizational factors and adherence to LTVV. Results The study included 5719 patients; 3340 (58%) patients received LTVV. A greater number of hospital beds (absolute difference 7.43% [95% confidence interval 0.61–14.24%]; p = 0.038), use of structured checklist during multidisciplinary rounds (5.10% [0.55–9.81%]; p = 0.030), and presence of at least one nurse per 10 patients during all shifts (17.24% [0.85–33.60%]; p = 0.045) were the only three factors that had an independent association with adherence to LTVV. Conclusions Number of hospital beds, use of a structured checklist during multidisciplinary rounds, and nurse staffing are organizational factors associated with adherence to LTVV. These findings shed light on organizational factors that may improve ventilation in critically ill patients.